Pengaruh Dana Pihak Ketiga, BI Rate dan Inflasi Terhadap Penyaluran Kredit Pada PT. Bank Mandiri, Periode 2014(I) -2018(IV) - Vania Maria Sarmento Naro; Anak Agung Sri Purnami; I Gusti Ayu Athina Wulandari (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aims to determine the effect of third party fund, BI Rate and Inflation on lending at Mandiri Bank. Data collection is obtained by collecting data published by the Financial Services Authority, Indonesia Bank and Mandiri Bank. This study used time series data and analyzed using multiple linear regression analysis techniques, namely to determine the effect of independent variables on the dependent variable using hypothesis testing, namely simultaneous test (F Test) and partial test (t test). The result of the F test indicate that the variable third party funds, the BI Rate and Inflation have a significant effect on lending at Mandiri Bank, with a significance level (0.000<0.05). The t test results show the partially Third Party Fund have a positive and significant effect with a significance level (0.000<0.005), BI Rate has a positive and insignificant effect with a significance level (0.395>0.005) and Inflation has a negative and insignificant effect with a significance level (0.059>0.05) on lending to Mandiri Bank.